Regional Economic Outlook, April 2013, Asia and Pacific : Shifting Risks, New Foundations for Growth. (Regional Economic Outlook, 2013)
Growth in the Asia-Pacific region shows signs of improving as extreme risks emanating from advanced economies have receded and domestic demand remains resilient, supported by relatively easy financial conditions and robust labor markets. A small and gradual pick-up in growth to over 5 3/4 percent is projected in the course of 2013. Risks to the outlook from within the region, such as rising financial imbalances and asset prices in some economies, are coming clearer into focus. Although Asia's banking and corporate sectors have solid buffers, monetary policymakers should stand ready to respond early and decisively to shifting risks, and macroprudential measures will also have a role to play. In many Asian economies, some fiscal consolidation could also rebuild the space needed to respond to future shocks and preempt potential overheating pressures from capital inflows. In particular, there is a growing need to make tax and spending policies more efficient. To sustain high growth rates and alleviate the 'middle-income trap' across Emerging Asia, the policy agenda will vary by jurisdiction but will also often include strengthening infrastructure investment and reforming goods and labor markets.